PENDANAAN BOOTSTRAP UNTUK MENDORONG SUSTAINABILITY BISNIS PADA UKM PENGOLAHAN KERUPUK IKAN HARUAN DI LAHAN BASAH KALIMANTAN SELATAN - Widyarfendhi; Dalimunthe, Fahmi Roy (JWM (JURNAL WAWASAN MANAJEMEN), 2023)
Snakehead fish (haruan) is one of the favorite fish commonly consumed by people in South Kalimantan. However, the condition of supply, where the majority comes from catches, makes the price of this fish fluctuate, and it is not uncommon for the price to soar. Availability of supply and price volatility are obstacles faced by SMEs processing haruan fish crackers. To ensure continuous production, the availability of bootstrap funding is expected to reduce problems with the availability of raw material supplies due to price fluctuations. This study aims to analyze: (1) how the application of bootstrap funding to SMEs processing haruan fish crackers in South Kalimantan, and (2) how the bootstrap funding strategy can affect the business sustainability of SMEs processing haruan fish crackers in South Kalimantan. Information collected through questionnaires and interviews from 30 samples of Haruan cracker processing SMEs in South Kalimantan, which was then analyzed using a quantitative approach with SEM PLS. The results of this study indicate that, of the seven alternative bootstrap funding methods, asset management and customers are the two sources of bootstrap funding that have a negative effect on business sustainability. Other sources consisting of employees, owners, suppliers and networks, have no effect on business continuity even though they have a positive direction.